Drug safety assurance through clinical genotyping: near-term considerations for a system-wide implementation of personalized medicine. (July 2008) - Kane, Michael D; Springer, John A; Sprague, Jon E
The rationale and overall system-wide behavior of a clinical genotyping information system (both DNA analysis and data management) requires a near-term, scalable approach, which is emerging in the focused implementation of pharmacogenomics and drug safety assurance. The challenges to implementing a successful clinical genotyping system are described, as are how the benefits of a focused, near-term system for drug safety assessment and assurance overcome the logistical and operational challenges that perpetually hinder the development of a societal-scale clinical genotyping system. This rationale is based on the premise that a focused application domain for clinical genotyping, specifically drug safety assurance, provides a transition paradigm for both professionals and consumers of healthcare, thereby facilitating the movement of genotyping from bench to bedside and paving the way for the adoption of prognostic and diagnostic applications in clinical genomics.